Betaine supplementation for finishing cattle - Löest, C.A.; Coetzer, C.M.; Hunter, R.D.; Lambert, B.D.; Titgemeyer, Evan C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred heifers (756 lb) were used to evaluate the effects of feed-grade betaine on animal performance and carcass characteristics. Heifers had ad libitum access to a finishing diet without betaine or with 4, 8, or 12 g/day of feed-grade betaine top-dressed at feeding. Feed intakes, gains, and feed efficiencies were not significantly altered by feed-grade betaine. Hot carcass weights tended to increase with the betaine supplementation, but dressing percent; percentage of kidney, pelvic and heart fat; fat thickness; or ribeye area were not altered. Yield grades were numerically greater, and marbling scores significantly greater for heifers supplemented with 4 or 12 g/day of betaine. These results demonstrate that supplementation of feed-grade betaine may have minor effects on performance and carcass characteristics.
Keywords: Beef; Betaine; Heifers; Performance; Carcass